(untitled) (Nigerian Journal of Technology, 2021)
Major urban cities in the developing countries are faced with the peculiar problem of poor air quality, which has resulted into millions of untimely death as well as other adverse environmental impacts including climate change. To combat this negative trend, regular documentation of the emission rates and concentrations of the various air pollutants has been identified as a suitable means of designing a sound mitigation approach. Here, we estimated the emission rates of criteria air pollutants (CAPs) and greenhouse gases (GHGs) generated from an industrial setting; as well as the associated environmental impact on local air quality, using emission inventory methodology and air dispersion model. In the study area, the energy consumption pattern was reported and the emission rates of associated gaseous pollutants were observed to range from 0.22 to 85500 kg/day. Similarly, the concentrations of major pollutants were observed to be within the thresholds stipulated by the World Health Organization. http://dx.doi.org/10.4314/njt.v40i1.19